Association Between Alcohol Consumption and the Risk of Type 2 Diabetes Mellitus Across Different Body Mass Index Categories Among Japanese Workers - Yu Wang; Yosuke Inoue; Shohei Yamamoto; Ami Fukunaga; Shuichiro Yamamoto; Toru Honda; Tohru Nakagawa; Takeshi Hayashi; Maki Konishi; Tetsuya Mizoue (Journal of Epidemiology)
Background: While evidence from Western countries links low-to-moderate alcohol consumption to a lower risk of type 2 diabetes mellitus (T2D), findings have been inconsistent in Asia. Since T2D in Asia involves both insulin resistance and deficient insulin secretion, both of which are differently affected by alcohol, we prospectively examined whether the association differs according to body mass index (BMI) categories among the Japanese. Methods: Participants were 31,524 health checkup examinees (26,819 males and 4,705 females aged 20–64 years) who were free from diabetes at baseline. Self-reported data on alcohol use were used to estimate the average daily alcohol consumption at the baseline. Incident diabetes was identified at annual checkups during the follow-up period. A Cox proportional hazards model was used to estimate hazard ratios and 95% confidence intervals. Results: During a median follow-up of 12.0 years, 3,527 male and 287 female participants developed T2D. The association between alcohol consumption and T2D risk differed markedly by BMI in both sexes. Among males, low- and moderate-level alcohol consumption was associated with a lower T2D risk in individuals with BMI ≥25.0 kg/m2, whereas consumption at a level of 2 go/day (approximately 46 g ethanol) was linked to an increased T2D risk in those with BMI ≤22.0 kg/m2. In females, similar patterns were observed, although confidence intervals were broad due to the smaller sample size. Conclusion: In Japan, low-to-moderate alcohol consumption may lower T2D risk in those with excess body weight, while high alcohol consumption may increase T2D risk in those with lower BMI.